Financial Ratio Analysis as Determinant of Financial Performance in Plantation Sector Companies Listed on the Indonesia Stock Exchange - Marisa Eka Prasetyawati; Dika Muftia (International Journal of Multi Discipline Science (IJ-MDS), 2025)
This study aims to determine the financial performance of plantation sector companies listed on the Indonesia Stock Exchange through financial ratio analysis. This study used a quantitative study with a descriptive approach. The sample consisted of 16 plantation sector companies listed on the Indonesia Stock Exchange with predetermined criteria. The data of this study were the company’s annual report, especially the financial report. The data were analysed using financial ratios, specifically employing net profit margin, current ratio, and debt to equity ratio to assess financial performance. The results showed that several companies achieve and exceed industry standards. This finding suggest if these companies demonstrate good financial performance and exhibit the capability for managing companies’ resources efficiently and effectively.